Advertising and investment spillovers in the diffusion of residential energy efficiency renovations - Matthew Collins; John Curtis (The Economic and Social Research Institute (ESRI), 2017)
This paper examines the diffusion of energy efficiency retrofits across the national housing stock and specifically examines whether the level of applications for subsidy support is impacted by advertising, either online or through print and radio media, and whether there are spillover effects from prior investments in retrofits on new retrofit subsidy applications. While there are numerous drivers of household retrofitting activities, the focus here is specifically on advertising and spillover effects. The analysis employs a Bass growth model using a subsidy scheme administrative dataset from Ireland. The research finds that some but not all advertising related to a retrofit subsidy scheme increases the level of scheme applications and also that there are spillover effects from a niche retrofit scheme targeting communities (covering both private and community buildings) on private applications for energy efficiency subsidy support.
Keywords: 330